Is the European Health Interview Survey online yet? Response and net sample composition of a web-based data collection. (7th November 2019) - Braekman, Elise; Charafeddine, Rana; Demarest, Stefaan; Drieskens, Sabine; Tafforeau, Jean; Van der Heyden, Johan; Van Hal, Guido
Abstract: Background: The European Health Interview Survey (EHIS) provides cross-national data on health status, health care and health determinants. So far, 10 of the 30 member states (MS) opted for web-based questionnaires within mixed-mode designs but none used it as the sole mode. In the context of future EHIS, the response rate and net sample composition of a web-only approach was tested. Methods: A Belgian study with a target sample size of 1000 (age: 16–85) was organized using the EHIS wave 3 model questionnaire. The sample was selected according to a multistage, clustered sampling procedure with geographical stratification. Field substitution was applied; non-participating households were replaced by similar households regarding statistical sector, sex and age. There was one reminder letter and a €10 conditional incentive. Results: Considering all substitutions, a 16% response rate was obtained after sending one reminder. Elderly, Brussels Capital inhabitants, people living without a partner and those with a non-Belgian nationality were less responding. By design, there were no differences between the initial and final net sample regarding substitution characteristics. Nevertheless, people living without a partner, non-Belgians and lower educated people remain underrepresented. Conclusion: There was a low response rate, particularly for some population groups. The response rate was lower than those of MS using mixed-mode designs including web, especially these comprising interviewer-based approaches. Despite the long and complex questionnaire, there was a low break off rate. So far, web-only data collection is not an acceptable strategy for population-based health surveys but efforts to increase the response should be further explored.